2009
DOI: 10.1155/2009/159845
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in Food Allergy: Evidence from the PubMed Database

Abstract: Food allergies are potentially fatal immune-mediated disorders that are growing globally. The relationship between sex and food allergy remains incompletely understood. Here we tested the hypothesis that, should sex influence the clinical response to food allergens, this would be reflected by a sex disparity in published studies of food allergy. We performed a systematic search of the PubMed literature for IgE-mediated allergy to 11 allergenic foods of international regulatory importance. No date restriction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
55
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 38 publications
(44 reference statements)
7
55
1
2
Order By: Relevance
“…In recent studies, in agreement with our results, male gender [26], infantile eczema [27] and a family history of atopy [28,29] have been determined as important risk factors for the development of FA. Moreover, many studies have shown an association with AD.…”
Section: Discussionsupporting
confidence: 91%
“…In recent studies, in agreement with our results, male gender [26], infantile eczema [27] and a family history of atopy [28,29] have been determined as important risk factors for the development of FA. Moreover, many studies have shown an association with AD.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, male gender, eczema, other food allergies, and asthma were more frequently seen in association with positive WIgE, partly confirming previous results [2, 33]. …”
Section: Discussionsupporting
confidence: 88%
“…De los pacientes, la mayoría fue del sexo masculino (56.7 %), tendencia que persistió en el resto de las patologías alérgicas y concuerda con los datos evidenciados en la mayoría de la literatura internacional. 5,6,7,8,9,10,11,12 En un estudio regional previo no se identifi có diferencia en la prevalencia de rinitis y asma en la población preescolar entre hombres y mujeres. 4 Un aspecto importante es el análisis de los regí-menes de aseguramiento.…”
Section: Discussionunclassified